2012
DOI: 10.1080/03081087.2011.576343
|View full text |Cite
|
Sign up to set email alerts
|

Lie derivable mappings on prime rings

Abstract: Abstract. Let R be a prime ring containing a nontrivial idempotent. Suppose that a mapping δ : R → R satisfiesfor all a, b ∈ R. Then there exists a z a,b (depending on a and b) in its center

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Mathieu and Villena [17] gave the characterizations of Lie derivations on C * -algebras. W. Jing and F. Lu [13] showed that every Lie derivable map on a 2-torsion free prime ring R can be expressed as L = d + τ , where d is a derivation of R into its central closure T and τ : R → C (where C is extended centroid of R) is nearly additive i.e. τ (X +Y ) = τ (X)+τ (Y )+Z X,Y where Z X,Y ∈ Z(R) (depends on X and Y in R) and vanishes on each commutator.…”
Section: Introductionmentioning
confidence: 99%
“…Mathieu and Villena [17] gave the characterizations of Lie derivations on C * -algebras. W. Jing and F. Lu [13] showed that every Lie derivable map on a 2-torsion free prime ring R can be expressed as L = d + τ , where d is a derivation of R into its central closure T and τ : R → C (where C is extended centroid of R) is nearly additive i.e. τ (X +Y ) = τ (X)+τ (Y )+Z X,Y where Z X,Y ∈ Z(R) (depends on X and Y in R) and vanishes on each commutator.…”
Section: Introductionmentioning
confidence: 99%
“…Mathieu and Villena [15] gave the characterizations of Lie derivations on C * -algebras. W. Jing and F. Lu [8] showed that every Lie derivable mapping on a 2-torsion free prime ring R can be expressed as d = ψ + ξ, where ψ : R → T is an additive derivation and ξ : R → C is nearly additive i.e. ξ(U…”
Section: Introductionmentioning
confidence: 99%
“…Also, Li, Chen and Wang [9] obtained the same result for * -Lie derivable mappings on von Neumann algebras and proved that every * -Lie derivable mapping on a von Neumann algebra with no central abelian projections can be expressed as the sum of an additive * -derivation and a mapping with image in the centre vanishing on commutators. In addition, the characterization of Lie derivations and * -Lie derivations on various algebras are considered in [1], [2], [5], [4], [6], [8], [12], [13], [17], [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let A be an algebra over a commutative ring R. Recall that an R-linear mapping [1], [2], [5], [6], [7], [8], [11], [12], [15], [18]). …”
Section: Introductionmentioning
confidence: 99%